Peranan Digital Marketing Guna Mengatasi Target Penjualan Di PT. Impero Nusa Pratama Bekasi (Current Research in Education: Conference Series Journal, 2023)
In the era of very tight business competition, every company is required to develop a business strategy in order to compete with other competitors. One thing that is very important is to face the situation of the flow of production and development of goods and expand its business. PT. Impero Nusa Pratama Bekasi is a company engaged in Supply Engineering Service which was established in 2014. Its main objective is to improve service, cost efficiency, and work effectiveness that will be provided to the organization concerned. In implementing the system at PT. Impero Nusa Pratama In this study, the author analyzes a website-based digital marketing model and helps develop an existing system with various product features that are marketed through display and marketing. even more advanced digital like SEO. The method used is a survey and literature study based on a review of the existing literature. This study also uses various sources and references related to the company. Even the existence of Business intelligence can overcome the sales target of the company.